(untitled) (Historia, 2021)
This paper argues for the importance of ecumenism as part of the understanding of the global anti-apartheid struggle. Specifically, the paper explores the symbolism and effects of the World Council of Churches’ (WCC) decision to fund southern African liberation movements, through the Programme to Combat Racism (PCR) in September 1970. It presents a qualitative analysis of the responses to the grants in South Africa and Botswana, pointing to the mixed results of its funding of the liberation movements and the responses it received in these countries. Reflection on the WCC grants provides insight into a significant element of international pressure on the apartheid regime, in the form of the international ecumenical movement, and an opportunity to contrast South Africa with its northerly neighbour, Botswana. This comparison highlights that the funding to the liberation movements was a political step rather than a purely theological controversy as it has tended to be relegated to through neglect in the mainstream South African historiography.